1982
DOI: 10.1104/pp.69.4.814
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Increase in the Number and Activity of Ribosomes Bound to Pea Chloroplast Thylakoids in Vivo

Abstract: Some of the chloroplast 70S ribosomes are seen in electron micrographs to be associated with the thylakoid membranes (5, 9, 19, 28). At least some of these ribosomes must be associated with mRNA, since washed thylakoids are capable of synthesizing proteins when supplemented with soluble factors (1,2,8,20). Retention in the thylakoids of the newly synthesized peptides provided evidence that the proteins synthesized were discharged into the membranes (2,20). From this, it seemed likely that the ribosomes active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…This change is particularly dramatic in the case of 16s rRNA, which is normally a very stable RNA (Kim et al, 1993). The decline of pea ribosomes during light-induced chloroplast development in pea was previously reported (Fish and Jagendorf, 1982). Most plastid proteins are very stable; therefore, there is little reason to maintain the full capacity to synthesize plastid proteins once leaf and chloroplast development is complete.…”
Section: Differential Expression Of Plastid Cenes During Leaf Developmentioning
confidence: 80%
“…This change is particularly dramatic in the case of 16s rRNA, which is normally a very stable RNA (Kim et al, 1993). The decline of pea ribosomes during light-induced chloroplast development in pea was previously reported (Fish and Jagendorf, 1982). Most plastid proteins are very stable; therefore, there is little reason to maintain the full capacity to synthesize plastid proteins once leaf and chloroplast development is complete.…”
Section: Differential Expression Of Plastid Cenes During Leaf Developmentioning
confidence: 80%
“…While light in vivo can cause a net 25 to 75% increase in thylakoid-bound polysomes in pea chloroplasts (9), in most of our experiments in organello illumination only slowed down the extent of RNA loss during incubation (Table I). This was true for chloroplasts taken from plant in the light or in the dark.…”
Section: Rna Binding To Thylakoid Membranesmentioning
confidence: 85%
“…In previous work (9) it was found that 40 to 70% more RNA (the indicator for 70S ribosomes) was tightly associated with thylakoids isolated from pea plants in the light, than from plants in the dark. This was demonstrated to be a direct effect of light, preventable by DCMU, saturated at a very low light intensity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Euglena gracilis, EF-G is much more strongly light-regulated than EF-Tu [6], perhaps because many more copies of EF-Tu are required than EF-G. Fish and Jagendorf [9] noted an increase in puromycin sensitivity of thylakoid-bound ribosomes isolated from darkgrown pea seedlings exposed to a brief period (5 min) of illumination. This result is consistent with the notion that EF-G may be rate-limiting in dark-adapted chloroplasts, as nascent polypeptides would not be released by puromycin in the absence of translocation.…”
Section: Discussionmentioning
confidence: 99%